Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fimmu.2015.00407
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2 Channel-Mediated ROS-Sensitive Ca2+ Signaling Mechanisms in Immune Cells

Abstract: Transient receptor potential melastatin 2 (TRPM2) proteins form Ca2+-permeable cationic channels that are potently activated by reactive oxygen species (ROS). ROS are produced during immune responses as signaling molecules as well as anti-microbial agents. ROS-sensitive TRPM2 channels are widely expressed in cells of the immune system and located on the cell surface as a Ca2+ influx pathway in macrophages, monocytes, neutrophils, lymphocytes, and microglia but preferentially within the lysosomal membranes as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 61 publications
(74 reference statements)
2
70
0
Order By: Relevance
“…Since TRPM2 is a redox-sensitive channel (Hara et al, 2002;Perraud et al, 2005), a possible mechanism of phagosomal TRPM2 activation may involve generation of oxidants and the subsequent production of ADPR (Hara et al, 2002;Knowles et al, 2013;Perraud et al, 2005;Syed Mortadza et al, 2015;Toth and Csanady, 2010;Wehage et al, 2002). We observed that the H 2 O 2 -activated current in Trpm2 +/+ BMDMs treated with an antagonistic analog of ADPR was reduced to the level seen in Trpm2 −/− BMDMs, suggesting that H 2 O 2 activated phagosomal TRPM2 through ADPR generation.…”
Section: (N=3) *P<005 (T-test) (Fg) Adpr Antagonism Increases Phamentioning
confidence: 66%
See 1 more Smart Citation
“…Since TRPM2 is a redox-sensitive channel (Hara et al, 2002;Perraud et al, 2005), a possible mechanism of phagosomal TRPM2 activation may involve generation of oxidants and the subsequent production of ADPR (Hara et al, 2002;Knowles et al, 2013;Perraud et al, 2005;Syed Mortadza et al, 2015;Toth and Csanady, 2010;Wehage et al, 2002). We observed that the H 2 O 2 -activated current in Trpm2 +/+ BMDMs treated with an antagonistic analog of ADPR was reduced to the level seen in Trpm2 −/− BMDMs, suggesting that H 2 O 2 activated phagosomal TRPM2 through ADPR generation.…”
Section: (N=3) *P<005 (T-test) (Fg) Adpr Antagonism Increases Phamentioning
confidence: 66%
“…Transient receptor potential melastatin 2 (TRPM2), a redoxsensitive non-selective cation channel localized in the plasma membrane (Hara et al, 2002;Knowles et al, 2013;Perraud et al, 2001Perraud et al, , 2005Syed Mortadza et al, 2015;Toth and Csanady, 2010), plays an important role in bacterial clearance due in part to its ability to activate cytokine generation (Knowles et al, 2011;Qian et al, 2014). Impaired production of cytokines in Trpm2 −/− mice led to high mortality following Listeria monocytogenes (LM) challenge (Knowles et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As introduced above, studies over the past years have shown that the Ca 2+ -permeable TRPM2 channel on the cell surface acts as a major molecular mechanism for ROS-induced Ca 2+ signalling in immune cells80. An early study reported that exposure of microglial cells to H 2 O 2 induced an increase in the [Ca 2+ ] c 73 but it was not clearly understood how important the TRPM2 channel was in mediating ROS-induced Ca 2+ signalling.…”
Section: Discussionmentioning
confidence: 99%
“…A role for TRPM2 in ROS-associated cell death has been noted in various cell types including cerebral cortical neurons and myocytes (17, 41). TRPM2 has been linked to inflammasome assembly (42) and ischemia-reperfusion–induced cellular injury (43).…”
Section: Discussionmentioning
confidence: 99%